2023
DOI: 10.3389/fimmu.2023.1095098
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying neutrophil-associated subtypes in ulcerative colitis and confirming neutrophils promote colitis-associated colorectal cancer

Abstract: BackgroundUlcerative colitis (UC) is a chronic inflammatory disease of the intestinal mucosa, the incidence of which has increased worldwide. There is still a lack of clear understanding of the pathogenesis of ulcerative colitis that ultimately leads to colitis-associated colorectal cancer.MethodWe download UC transcriptome data from the GEO database and pass the limma package in order to identify differentially expressed genes. Gene Set Enrichment Analysis (GSEA) was used to identify potential biological path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…The high inflammation subtype, identified in three studies [58] , [76] , [102] , is characterized by marked inflammatory features, including significant enrichment in inflammation and immune-related pathways such as interferon-γ/α response, TNF-α signaling pathway, IL-6 JAK-STAT3 signaling pathway [102] , and others including complement and coagulation cascades, cytokine-cytokine receptor interaction, and Toll-like receptor signaling pathway [76] . It also involves the upregulation of proinflammatory markers at the mRNA level, such as S100A8, S100A9, TNF-α, IL-1β, IL-6, IL-17, INF-γ.…”
Section: The Review Of the Molecular Subtypes Biological Results For ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The high inflammation subtype, identified in three studies [58] , [76] , [102] , is characterized by marked inflammatory features, including significant enrichment in inflammation and immune-related pathways such as interferon-γ/α response, TNF-α signaling pathway, IL-6 JAK-STAT3 signaling pathway [102] , and others including complement and coagulation cascades, cytokine-cytokine receptor interaction, and Toll-like receptor signaling pathway [76] . It also involves the upregulation of proinflammatory markers at the mRNA level, such as S100A8, S100A9, TNF-α, IL-1β, IL-6, IL-17, INF-γ.…”
Section: The Review Of the Molecular Subtypes Biological Results For ...mentioning
confidence: 99%
“…NETs may also intensify autoimmune diseases like rheumatoid arthritis and systemic lupus erythematosus [75] . Thus, in a study on ulcerative colitis (UC) subtype study, researchers determined subtypes based on neutrophil-associated differential expression genes [76] . Initially, the limma [77] tool was used to identify DEGs between disease and normal controls.…”
Section: Molecular Level Classification Methods Of Autoimmune Diseasesmentioning
confidence: 99%
“…Daniel Triner et al suggested that neutrophils could impede colon tumor growth and progression by limiting bacterial populations and tumor-associated inflammatory responses 21 . Conversely, Zhang et al suggested that neutrophils might promote colitis-associated colon carcinogenesis 48 . Moreover, Rayes et al found evidence that NETs could facilitate targeted metastasis in colon cancer 49 .…”
Section: Discussionmentioning
confidence: 99%
“…UC has become a common digestive disease, and its recurrent episodes have been considered to increase the risk of colon cancer. 22 However, current treatment drugs for UC have limited their application due to their toxicity and side effects. 4 Consequently, dietary compounds are attracting more and more attention due to their advantages in treating diseases with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%